A novel oyster shell biocomposite for the efficient adsorptive removal of cadmium and lead from aqueous solution: Synthesis, process optimization, modelling and mechanism studies - Adeleke A.O.; Royahu C.O.; Afolabi A.A.; Alshammari M.B.; Imteaz M. (Public Library of Science, 2025)
This study highlights the effectiveness of oyster shell biocomposite for the biosorption of Cd(II) and Pb(II) ions from an aqueous solution. The aim of this work was to modify a novel biocomposite derived from oyster shell for the adsorption of Cd(II) and Pb(II) ions from aqueous solution. The studied revealed the specific surface BET surface area was 9.1476 m2/g. The elemental dispersive x-ray analysis (EDS) indicated that C, O, Ag, Ca were the predominant elements on the surface of the biocomposite after which metals ions of Cd and Pb were noticed after adsorption. The Fourier transform Irradiation (FT-IR) revealed the presence of carboxyl and hydroxyl groups on the surface. The effect of process variables on the adsorption capacity of the modified biocomposite was examined using the central composite design (CCD) of the response surface methodology (RSM). The process variables which include pH, adsorbent dose, the initial concentration and temperature were the most effective parameters influencing the uptake capacity. The optimal process conditions of these parameters were found to be pH, 5.57, adsorbent dose, 2.53 g/L, initial concentration, 46.76 mg/L and temperature 28.48C for the biosorption of Cd(II) and Pb(II) ions from aqueous solution at a desirability coefficient of 1. The analysis of variance (ANOVA) revealed a high coefficient of determination (R2 > 0.91) and low probability coefficients for the responses (P < 0.05) which indicated the validity and aptness of the model for the biosorption of the metal ions. Experimental isotherm data fitted better to the Langmuir model and the kinetic data fitted better to the pseudo-second-order model. Maximun Cd(II) and Pb(II) adsorption capacities of the oyster shell biocomposite were 97.54 and 78.99 mg/g respectively and was obtained at pH 5.56 and 28.48C. This investigation has provided the possibility of the utilization of alternative biocomposite as a sustainable approach for the biosorption of heavy metal ions from the wastewater stream. ? 2024 Adeleke et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.